71.2k views
5 votes
If f(x)=x^2+2x-3 and g(x)=x^2-9, find (f/g)(4) and (f+g)(4)

User Ucarion
by
5.0k points

2 Answers

1 vote

Answer: the first one is -11 and the second one is 0

Explanation:

someone answered your question but it was wrong so i had too guess and got the real answers since you know ... i ended up getting it wrong lol so yea

User Arynaq
by
5.1k points
2 votes

Answer:

Part 1: Find (f/g)(4) = 3

Part 2: Find (f+g)(4) = 28

Explanation:

Part 1: Find (f/g)(4):

(f/g)(4) means divide f function by g function and simplify it. Then plug in 4 into x of that simplified function.

Let's do this:


(x^2+2x-3)/(x^2-9)\\=((x+3)(x-1))/((x-3)(x+3))\\=(x-1)/(x-3)

Plugging in 4 into x gives us:


(x-1)/(x-3)\\=(4-1)/(4-3)\\=(3)/(1)\\=3

The answer is 3

Part 2: Find (f+g)(4):

(f+g)(4) means add f function and g function and simplify it. Then plug in 4 into x of that simplified function.

Let's do this:


(x^2+2x-3)+(x^2-9)\\=2x^2+2x-12

Plugging in 4 into x gives us:


2x^2+2x-12\\=2(4)^2+2(4)-12\\=28

The answer is 28

User Sgtdck
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.